Solar and heat pump systems for houses. ([Place of publication not identified] : Ernst & Sohn, 2014)
The combination of heat pumps and solar components is a recent development and has great potential for improving the energy efficiency of house and hot water heating systems. As a consequence, it can enhance the energy footprint of a building substantially. This work compares different systems, analyses their performance and illustrates monitoring techniques. It helps the reader to design, simulate and assess solar and heat pump systems. Good examples of built systems are discussed in detail and advice is given on how to design the most efficient system.
Introduction / Jean-Christophe Hadorn -- Theoretical Considerations. System description, categorization, and comparison / Jörn Ruschenburg, Sebastian Herkel -- Components and thermodynamic aspects / Michel Y Haller, Erik Bertram, Ralf Dott, Thomas Afjei, Daniel Carbonell, Fabian Ochs, Andreas Heinz, Sunliang Cao, Kai Siren -- Performance and its assessment / Ivan Malenković, Peter Pärisch, Sara Eicher, Jacques Bony, Michael Hartl -- Laboratory test procedures for solar and heat pump systems / Christian Schmidt, Ivan Malenković, Korbinian Kramer, Michel Y Haller, Robert Haberl, Anja Loose, Sebastian Bonk, Harald Drück, Jorge Facão, Maria João Carvalho -- Practical Considerations. Monitoring / Sebastian Herkel, Jörn Ruschenburg, Anja Loose, Erik Bertram, Carolina de Sousa Fraga, Michel Y Haller, Marek Miara, Bernard Thissen -- System simulations / Michel Y Haller, Daniel Carbonell, Erik Bertram, Andreas Heinz, Chris Bales, Fabian Ochs -- Economic and market issues / Matteo D'Antoni, Roberto Fedrizzi, Wolfram Sparber -- Conclusion and outlook / Jean-Christophe Hadorn, Wolfram Sparber.
Keywords: Heat pumps; Heating; Hot-water heating; Solar heat pump; Heat pumps; Electronic books